Poly(propylene fumarate)/hydroxyapatite nanocomposite/black phosphorus nanosheet phosphate composites for enhanced bone repair - Xiaoxia Huang; Jiahan Chen; Rui Ma; Jianghua Wang; Yong Teng (Journal of Orthopaedic Surgery and Research)
Abstract Background Bone defects due to trauma, infections, congenital malformations, and tumor resection remain significant health challenges. The polymethyl methacrylate (PMMA) bone cement’s limitations in orthopedic applications arise from its lack of bioactivity and the toxicity of its monomers. Hydroxyapatite (HA) cement is widely used for bone reconstruction despite its inherent brittleness. Biodegradable poly(propylene fumarate) (PPF) is recognized for its exceptional performance in addressing these bone defects and providing adequate mechanical support. Black phosphorus (BP) nanosheets (BPNs) have attracted attention due to their unique puckered honeycomb lattice, broad absorption spectrum, high specific surface area, excellent antibacterial properties, and tunable bandgap. In this study, we developed a novel bone cement, PPF/HA/BP, via thermal crosslinking and conducted in vitro evaluation. Methods PPF was synthesized using a two-step approach, whereas BPNs were produced through a liquid-phase exfoliation technique. Then, PPF/HA/BP composite materials were created using a thermal crosslinking process, followed by a thorough examination of their mechanical characteristics, compatibility with cells, osteogenic activity, and degradation properties. Results PPF/HA/BP bone cement was designed by optimizing formulation to possess mechanical properties comparable to bone tissue. PPF bone cement had a polymerization time of 8.16 ± 0.35 min and a temperature of 62.67 ± 0.67 °C. HA reduced polymerization time and temperature. PPF/HA/BP exhibited a polymerization time of 6.70 ± 0.10 min and a maximum temperature of 52.5 °C (P < 0.05). PPF/HA/BP enhanced the adhesion, proliferation, and mineralization of preosteoblasts on its surface and demonstrated photothermal properties. When exposed to an 808 nm laser, the bone cement’s temperature rose to 50ºC. After co-culturing with MC3T3-E1 for 14 days, the PPF/HA/BP group exhibited significantly higher expression of ALP, COL I, and RUNX2 compared to the PPF and PPF/HA groups (P < 0.05). However, no statistically significant difference was observed in the expression of ALP, COL I, and RUNX2 between the PPF and positive control groups (P > 0.05). Conclusion Biodegradable PPF/HA/BP demonstrated satisfactory mechanical properties, degradation behavior, outstanding photothermal characteristics, excellent biocompatibility, and osteogenic activity. It also promoted bone regeneration by enhancing the proliferation and differentiation of MC3T3-E1 cells in vitro and upregulating the related genes’ expression.